Impact of E-Service quality on customer satisfaction towards shopee among generation y in the Post-Covid-19 Pandemic - Chan Yong Rou; Danieal Arif Salehan; Muhammad Solehin Mat Zian; Nur Aliana Mahyaddin; Nur Shazwani Sabri (2023)
The impact of e-service quality on customer satisfaction towards Shopee among generation Y in the post-Covid-19 pandemic will be the focus of this study. In this research, researchers looked into the connections between privacy, efficiency, fulfillment and website design with customer satisfaction. This study also has chosen generation Y as respondents to complement this study. In collecting respondent data, an online questionnaire form has been used because it is easy to connect, obtain and analyze data from all over Malaysia. Non-probability sampling has been applied in this study because the populations are unknown. In order to accomplish the objective of this study, a quantitative method will be used. Reliability, descriptive, correlation and multiple linear regression analysis have been used in this study. The result of the analysis confirmed that only two independent variables have a relationship with the dependent variable. It showed a positive and significant correlation exists between privacy and fulfillment with customer satisfaction. Besides, this study has identified some limitations of this research. As a result, recommendations have been made for additional investigation. Future researchers can therefore identify the strategies to enhance this problem for future study.